The Cosmology of Menoreh Customary Tradition in Indigenous People Perspective - Ahmad Arrozy; Masdar Faridl; Febri Edytya Salsabila; Zahra Nada Novalina; Siti Muhibah; Rizqina Mukarromah (Sodality: Jurnal Sosiologi Pedesaan, 2023)
The concept of indigenous peoples is a global concern in local development including by international institutions such as the International Labour Organization. One indicator of indigenous peoples is cosmological knowledge which often incorporates deep connections between the material, spiritual realms and emphasizes the connective interconnectedness between humans and nature. Its development later became an international convention to protect the existence of indigenous peoples. This research uses ethnographic methods to explore the cosmology and memorial story of Menoreh indigenous people who do not recognize the administrative boundaries of the district so that they can perform traditional ceremonies from an indigenous perspective. Menoreh’s landscape illustrates the cosmological relationship between the local market, the Baritan ceremony, and the conservation of spring sacralization, which is a sustainable customary praxis. The ritual element of the cosmological axis of social interaction leads to two concepts. First, the relationship between Menoreh (caretakers as indigenous actors) and pilgrims' actions as visitors becomes an elementary social interaction. Second, the tradition of offerings and memorial of spirits (petilasan) becomes an elementary symbolic form.